Some karst spring analysis at the piedmont of Bükk Mountains - Kürti Lívia (Acta climatologica, 2005)
Sok karsztforrás található a Bükk-hegységben, amelyek közül néhány, mint a Kács-Sályi vízrendszer jelentős szerepet játszik a Borsodi-régió vízellátásában. Előfordul itt langyos vizű, kevert vizű és hideg vizű forrás is. A rendszer működésének tanulmányozása céljából mintát gyűjtöttünk ezekből a forrásokból és néhány vízfolyásból. Elemeztük a víz teljes keménységét, Ca2+ és Mg2 * tartalmát, valamint a klorid, nátrium, kálium, foszfát, nitrát, szulfát és nehézfémtartalmát. Különbség mutatkozott a források között. A tanulmány bemutatja a vizsgált területet és a kutatást There are several karst springs in the Bükk Mountains. Some of these, like the system of Kács and Sály, have in important role in the drinking water supply system in the region of Borsod. Here we can find springs with lukewarm water, springs with mixed water and cold water springs. We have sampled these springs and some streams in order to leam how the system works. We analysed the total hardness, the Ca2+ and Mg2+ contents, and also the content of chloride, sodium, potassium, phosphate, nitrate, sulphate and heavy metals. There are some differences between these springs. In this article we give some general information about the research and the study area.